IN VITRO ZYGOTIC EMBRYO CULTURE OF AN ECONOMICALLY IMPORTANT FOREST TREE SPECIES GMELINA ARBOREA ROXB. - M. RAMBABU; D.UJJWALA; N. RAMA SWAMY (International Journal of Pharma and Bio Sciences, 2016)
Gmelina arborea is an economically important forest tree species. The wood of this species is very valuable for making furniture, general carpentry and constructions. This plant also has medicinal value in Ayurvedic formulations for treating various diseases. In the present investigation, the zygotic embryos of G.arborea were cultured on ½MS,MS,WPM and B5 medium containing various sucrose levels (7.5-40 g/l) supplemented with different concentrations of auxins (2,4-D/IAA/IBA/NAA) and also with GA3. Maximum percentage (95%) of zygotic embryo germination was observed at MS medium containing 30 g/l sucrose supplemented with 1.0 mg/l GA3 compare with all other combinations and concentrations. Embryo orientation technique also effected the germination.